2009
DOI: 10.1158/1055-9965.epi-08-0416
|View full text |Cite
|
Sign up to set email alerts
|

Family History, Genetic Testing, and Clinical Risk Prediction: Pooled Analysis of CHEK2*1100delC in 1,828 Bilateral Breast Cancers and 7,030 Controls

Abstract: If breast cancers arise independently in each breast the odds ratio (OR) for bilateral breast cancer for carriers of CHEK2*1100delC should be f5.5, the square of the reported OR for a first primary (OR, 2.34). In the subset of bilateral cases with one or more affected relatives, the predicted carrier OR should be f9. We have tested these predictions in a pooled set of 1,828 cases with 2 primaries and 7,030 controls from 8 studies. The second primary OR for CHEK2*1100-delC carriers was 6.43 (95% confidence inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 28 publications
2
34
1
1
Order By: Relevance
“…5,[13][14][15][16][17][18][19] For homozygous carriers, our observations indicate that (contralateral) breast cancer risk may be as high as to justify preventive mastectomy (or at least intensified screening), but longitudinal studies on more cases are needed to arrive at more accurate risk estimates.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…5,[13][14][15][16][17][18][19] For homozygous carriers, our observations indicate that (contralateral) breast cancer risk may be as high as to justify preventive mastectomy (or at least intensified screening), but longitudinal studies on more cases are needed to arrive at more accurate risk estimates.…”
Section: Discussionmentioning
confidence: 93%
“…Homozygous wild-type patients are all homozygous wild-type patients from the ORIGO cohort for whom follow-up was available. 15,18,20 In 1100delC homozygotes, this risk seems comparable or even higher, with potential consequences for clinical management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the BRCA1 and BRCA2 proteins were cloned and their association with family breast cancer was detected (Miki Y et al, 1994;Wooster R et al, 1995), greater emphasis was placed on the candidate gene of breast cancer. The cell cycle-checkpoint kinase 2 gene, or CHEK2, was widely researched as a strong candidate gene for breast cancer susceptibility (Vahteristo et al, 2002;Sodha et al, 2002;Offit et al, 2003;CHEK2 Breast Cancer Consortium, 2004;Dufault et al, 2004;Friedrichsen et al, 2004;Mateus Pereira et al, 2004;Baeyens et al, 2005;Kleibl et al, 2005;Rashid et al, 2005;Bernstein et al, 2006;Einarsdóttir et al, 2006;Cybulski et al, 2007;Weischer et al, 2007;Zhang et al, 2008;Fletcher et al, 2009;McInerney et al, 2010;Iniesta et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Various sporadic and hereditary cancers in human are reported to be caused by mutations in gene CHEK2 Chaturvedi et al, 1999;Matsouka et al, 2000;Ingvarsson et al, 2002;Craig and Hupp, 2004;Bartek, Hollestelle et al, 2010and Lukas, 2003and Nevanlinna and Bartek, 2006. CHEK2 1100delC most widely been study and suggested to increase the risk of breast cancer in women who have a positive family history of breast cancer, however this mutation has not been reported in Asian populations (Wu et al, 2001;Weischer et al, 2008;Fletcher et al, 2009;Baloch et al, 2014). Different missense mutations other than 1100delC may lead to loss of function and cause cancer (Narod, 2010 andLe Calviz-Kem et al, 2011).…”
Section: Introductionmentioning
confidence: 99%